Surgical management of acute intestinal obstruction study of 50 cases operated in emergency - Lad, Vipul; Bochiya, Girish; Tailor, Vasu (International Surgery Journal, 2023)
Background: Intestinal obstruction is one the major cause that patients underwent emergency operations and which might lead to complications that could be turn fatal. Prompt evaluation and treatment prevents mortality and morbidity of post-operative patients. Methods: Prospective study conducted between 01 April 2020 to 31 March 2022 in 50 patients of intestinal obstruction operated in emergency according to inclusion criteria. Pre-operative, intraoperative, and post-operative assessment and recording of data done. Results: In 50 cases of intestinal obstruction, commonest age group is 41 to 60 years, pain and obstipation remains major presenting symptoms and tenderness, guarding and rigidity were most common signs. The commonest cause of intestinal obstruction in the adults in this study was postoperative adhesions (44%) followed by Koch’s abdomen (30%). Malignancy of the large bowel was seen in 6 cases constituting 12% of cases, obstructed hernia in 5 cases (10%), intussusception in 3 cases (6%) and gut malrotation in 1 case (2%). Comorbidity like hypertension and diabetes were main causes of post-operative complications. Conclusions: Maximum incidence of intestinal obstructions were reported in Age group 41-60 years with male predominance. Abdominal pain was the consistent symptoms followed by obstipation. Post-operative adhesion were the most common cause of the intestinal obstruction. Malignancy and multiple comorbidity remains the major risk factor for the post-operative complications and mortality.